1987
DOI: 10.1038/328170a0
|View full text |Cite
|
Sign up to set email alerts
|

A new oncogene in human thyroid papillary carcinomas and their lymph-nodal metastases

Abstract: Using DNA transfection analysis on NIH 3T3 cells, activated human oncogenes have been isolated from a variety of fresh solid tumours. Thyroid neoplasias show a wide range of lesions varying from slowly progressive well-differentiated tumours to anaplastic highly malignant neoplasms. Therefore they represent an attractive model to investigate the role of oncogene activation in different stages of the neoplastic state. Here we report the detection of transforming activity in DNAs extracted from five thyroid papi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
210
1
7

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(221 citation statements)
references
References 0 publications
3
210
1
7
Order By: Relevance
“…Initial reports suggested that RET/PTC was specific for PTC [183,184] but later it was also found in some benign lesions [185,186] and diseases such as Hashimato disease [187]. According to these results, RET/PTC is not a specific PTC marker.…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%
“…Initial reports suggested that RET/PTC was specific for PTC [183,184] but later it was also found in some benign lesions [185,186] and diseases such as Hashimato disease [187]. According to these results, RET/PTC is not a specific PTC marker.…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%
“…The ret gene, located on Chromosome 10q, encodes a transmembrane tyrosine kinase receptor (13)(14)(15). Ret is normally expressed in neural crestderived cells; normal thyroid follicular epithelial cells do not express ret (19).…”
Section: Figure 2 Immunohistochemistry For Ck19mentioning
confidence: 99%
“…However, in the majority of PCs, a gene rearrangement occurs that places the intracellular domain of the ret gene under the transcriptional control of one of several genes that are expressed in thyroid follicular epithelium (16). This chimeric gene, the ret/PTC oncogene, is specific to papillary carcinomas and encodes a protein product that contains the cytoplasmic portion of ret (13)(14)(15). Therefore, immunohistochemical detection of the carboxy terminus of the ret protein in thyroid follicular epithelial lesions serves as a reliable marker for papillary carcinoma (16).…”
Section: Figure 2 Immunohistochemistry For Ck19mentioning
confidence: 99%
See 1 more Smart Citation
“…For this cell line, cell scattering involves not only the loss of most intercellular junctions (but not all) and the dissociation of the cells from the epithelial layer, but also a cytoskeletal reorganization followed by an active migration [9,21,13]. Moreover the addition of the HGF induces cell polarization, forma-tion of branched tubules and makes the cellular colonies assume a stellar-shape configurations (see Fig.…”
Section: Introduction and Phenomenological Descriptionmentioning
confidence: 99%